2014
DOI: 10.1038/emm.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Role of the epithelial–mesenchymal transition and its effects on embryonic stem cells

Abstract: The epithelial–mesenchymal transition (EMT) is important for embryonic development and the formation of various tissues or organs. However, EMT dysfunction in normal cells leads to diseases, such as cancer or fibrosis. During the EMT, epithelial cells are converted into more invasive and active mesenchymal cells. E-box-binding proteins, including Snail, ZEB and helix–loop–helix family members, serve as EMT-activating transcription factors. These transcription factors repress the expression of epithelial marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 62 publications
(95 reference statements)
3
87
0
1
Order By: Relevance
“…S3I-V), including the activating transcription factor ZEB1 and the induced mesenchymal marker vimentin (Kim et al, 2014). This is consistent with animal studies in which EMT underpins the migration of EPDCs into the subepicardial layer, prior to contributing derivatives to the developing coronary arteries and interstitial fibroblasts (Sylva et al, 2014).…”
Section: Resultssupporting
confidence: 73%
“…S3I-V), including the activating transcription factor ZEB1 and the induced mesenchymal marker vimentin (Kim et al, 2014). This is consistent with animal studies in which EMT underpins the migration of EPDCs into the subepicardial layer, prior to contributing derivatives to the developing coronary arteries and interstitial fibroblasts (Sylva et al, 2014).…”
Section: Resultssupporting
confidence: 73%
“…For comprehensive review, refer to Kalluri andWeinberg (2009), Thiery et al (2009) and Peinado et al (2007). hESC were suggested to undergo EMT during cell differentiation; however, the underlying mechanism is not that much studied as compared to EMT in embryonic development and cancer (Kim et al 2014). Early studies revealed that cultivation of hESC on extracellular matrix-coated plates and fibroblast-conditioned medium results in morphological changes at the periphery of the colonies.…”
Section: Epithelial-to-mesenchymal Transition Differentiation and Stmentioning
confidence: 99%
“…It has been well established that during their pluripotent state, mESCs express high levels of cell adhesion proteins, most prominently E-cadherins [5][6][7]. This is unsurprising as preliminary formation of the ICM is heavily dependent on cell-cell interactions that dynamically form the physical properties of their microenvironment.…”
Section: Introductionmentioning
confidence: 99%